Skin test to assess virus-specific cytotoxic T-cell activity. - Kündig, T M (1992)
A way to assess specific CD8+ T-cell activity in a skin test analogous to the conventional delayed-type hypersensitivity (DTH) reaction for CD4+ T cells is presented. Local injection of viral class I binding peptides caused a specific CD8+ T-cell-mediated DTH in footpads of virally infected mice. The DTH was inducible only during the acute phase of the infection. Apparently because of the short half-life of locally available peptide, only activated CD8+ effector T cells could mediate the reaction. This skin test may prove to be particularly interesting for use in humans to evaluate the activation status of CD8+ T cells during acute viral infections and of memory CD8+ T cells, for example, in chronically active immunopathological disease or infection.